Key concepts in human resource management - Sutherland, Jonathan; Canwell, Diane (Palgrave key concepts, 2004)
Key Concepts in Human Resource Management is one of a range of comprehensive glossaries with entries arranged alphabetically for easy reference. All major concepts, terms, theories and theorists are incorporated and cross-referenced. Additional reading and Internet research opportunities are identified. More complex terminology is made clearer with numerous diagrams and illustrations. With over 500 key terms defined, the book represents a comprehensive must-have reference for anyone studying a business-related course or those simply wishing to understand what human resource management is all about. It will be especially useful as a revision aid.